Rise in Costs of Irrigation and Multipurpose Projects Report of the Expert Committee - Planning Commission (Planning Commission, 1973)
Since Independence, a large number of irrigation and multipurpose projects have been taken up for construction in the country. While the benefits of irrigation accruing from these projects have greatly helped in increasing agricultural production in the country, the mounting costs and the frequent revision of the project estimates and consequent -delay in the completion of the projects and accrual of the benefits therefrom have been causing great concern to the Government. There has been no scientific investigation so far into the causes leading to the large number of revisions in project estimates. The Government of India, therefore, decided to refer this question to a Committee of Experts so that a sound policy could be framed for formulation and implementation of future irrigation and multipurpose projects.
Ministry of Irrigation and Power Government of India
Ministry of Irrigation and Power Government of India